Low risk of concussions in top-level karate competition. Issue 4 (16th December 2016) - Arriaza, Rafael; Cierna, Dusana; Regueiro, Patricia; Inman, David; Roman, Franco; Abarca, Benjamin; Barrientos, Mercé; Saavedra, Miguel A
Abstract : Background: Although it is well known that injuries occur in combat sports, the true incidence of concussions is not clearly defined in the literature for karate competition. Aim: To determine the incidence of concussions in top-level (World Karate Federation World Championships) karate competition. Methods: Injuries that took place in 4 consecutive World Karate Championships (from 2008 to 2014) were prospectively registered. A total of 4625 fights (2916 in the male category and 1709 in the female category) were scrutinised, and concussions were identified and analysed separately for frequency (rate per fight) and injury risk. Results: A total of 4 concussions were diagnosed by the attending physicians after carrying out athlete examinations. Globally, there was 1 concussion in every 1156 fights, or 0.43/1000 athlete-exposures (AE). In male athletes, the rate of concussion was 1/5832 min of fighting, and in female athletes, it was 1/6836 min. OR for concussion in women is 0.57 (95% CI 0.06 to 5.47; z=0.489; p=0.6249) and risk ratio for concussions in men is RR 1.478 (95% CI 0.271 to 8.072), p=0.528, representing a higher risk of definite concussions in men than in women, but not statistically significant. There is not a significantly higher risk of concussions in team competition (no weight limit) when compared with individual competition (held with strict weight limits for each category). Conclusion: The risk of concussions in top-level karate competition is low, with a tendency for an increased risk for men and for competition without weight limits, but not statistically significant with respect to women or individual competition.